On Typical Flaws of the Transformer Models for Inrush Current Evaluation - Serhii Zirka; Yurii Moroz (Challenges and Issues of Modern Science)
For many decades, the main, if not the only, equivalent circuit of a single-phase transformer was its T-model. To avoid ambiguity and take into account the topology of the core and windings, we will use the terms inner and outer windings, instead of the primary and secondary windings. So, inductances LS1 and L′S2 are the so-called "leakage inductances" of the inner and outer windings, respectively, r1 and r′2 are their resistances. In order to reproduce hysteretic (quasi-static) properties of the core material and to account for the dynamic core losses and saturation, the magnetizing branch is represented by an ATP-inductor DHM, which implements, starting with 2019 version, a Dynamic Hysteresis Model (DHM).